National pride and tax compliance: A laboratory experiment using a physiological marker - Alison Macintyre; Ho Fai Chan; Markus Schaffner; Benno Torgler (Center for Research in Economics, Management and the Arts (CREMA), 2021)
This paper reports on a laboratory experiment designed specifically to test the influence of national pride on tax honesty while using a physiological marker to observe emotional responses to patriotic priming. Participants were exposed to one of three framing videos before earning income in a real effort task, and at each of 20 rounds (years) were given the chance to declare their taxable income. We find that psychological priming through exposure to symbols of Australian national pride and national identity had a positive effect on the level of tax compliance among Australian but not non- Australians. In addition, non-Australians report lower tax compliance ratios in the treatment groups than in the control group which may indicate an outgroup effect. When exploring the potential of a physiological marker of national pride we observe two different types of physiological responses to the activation and effects of national pride and its impact on tax compliance among Australians. Iconic images activate the parasympathetic nervous system while sports scenes activate the sympathetic nervous system, but both types of images and responses are positively associated with tax compliance. In addition, we find that non-Australians resident in the country for more than a year report a higher level of tax compliance, and that there are some similarities in heart rate variability (HRV) responses between Australian citizens born in the country and those born overseas who have been in Australia for a longer period. Overall, the results support the proposition that identifying with an ingroup at a national level is important for tax compliance.
Keywords: C91; H26; D91; C88; 330; National pride; Tax compliance; Heart rate variability; Laboratory experiment